An analysis of English professional goalkeeper match actions over two competitive seasons: Implications for the coaching process - Elleray, A.; Jones, G. (World Congress of Performance Analysis of Sport IX, 2012)
Traditionally the goalkeeper`s contribution to a football game has been associated with handling skills such as shot stopping and catching crosses. Previous studies within goalkeeping have predominantly focused on activity profiles (Di Salvo et al., 2008;) diving techniques (Spratford et al., 2009), penalty kicks and defensive technical actions within major tournaments, (Bar-Eli et al.,2006). However, as part of their new goalkeeping initiatives, FIFA have investigated goalkeeper`s `interventions` (FIFA, 2012). The study has scrutinsed forty three high profile competitive matches, discovering that 66% of the goalkeeper`s interventions involved their feet e.g: distributions from dead ball situations, back passes and kicking the ball from their hands. Very little research has been carried out in this area of goalkeeper match profiling and therefore it is the aim of the present study to further add to the limited evidence available and to consider implications for the coaching process. Match analysis: Ninety two games of a professional English football League Two level team, over two whole seasons, were analysed and the following parameters considered: Interventions with feet (Dribble and Drive; Goal Kick; Back Pass; Hand Kick); Interventions with hands (Save; Dealing with Crosses; Throw Out; Through Ball). Training analysis: A typical week of professional goalkeeper training was also examined through observation. The various training activities were monitored and the time allocated to each area calculated as a percentage. Match analysis: Goalkeepers intervened over twice as much with their feet as with their hands. Results for the 2009/10 season were: Interventions with feet 69% (Dribble and Drive 7%; Goal Kick 16%; Back Pass 24%; Hand Kick 22%); Interventions with hands 31% (Saves 16%; Cross 8%; Throw Out 2%; Through Ball 5%). The following season 2010/11 results reported: Interventions with feet 70% (Dribble and Drive 6%; Goal Kick 14%; Back Pass 29%; Hand Kick 21%); Interventions with hands 30% (Saves 14%; Cross 7%; Throw Out 5%; Through Balls 4%). Observational training analysis: The `typical week`s training` included time spent in the following activities: Intervention with hands specific training (specific shot stopping and handling sessions, 36%); Interventions with both hands and feet (Team based shooting, phase of play sessions, team shape and small sided games, 36%) and gym based sessions (28%). It is evident from the results that there is a clear discrepancy between what the goalkeepers actually do within a competitive situation and within training scenarios. Implications for coaches include: Structure of the training sessions need to reflect time devoted to specific match actions in order to create more realistic training environments; Further emphasis required on certain areas of the game (distribution as opposed to shot stopping and reaction training).